The Bangladesh labour code, 2006 - Halim, Md. Abdul; Rahman, Masum Saifur (Dhaka : CCB Foundation, 2007)
Social Science
Keywords: Bangladesh Lababour Code; Conditions of service; Employment; Adolescent employment; Maternity benefit; Health and hygiene; Safety